Early detection of Ganoderma boninense infection in oil palm based on expression of fatty acid biosynthesis pathway genes - Abdullah, Siti Nor Akmar; Alizadeh, Fahimeh; Chong, Pei Pei; Yusuf, Umi Kalsom (2011)
The present invention relates to a method for early detection of Ganoderma boninense infection in oil palm and a method for indicating protection from Ganoderma boninense by a bio-control agent in a palm based on expression profile of genes associated with fatty acid (FA) biosynthetic pathway using roots and vegetative tissues comprising the step of: collecting a root or vegetative tissue sample, grounding the root or vegetative tissue sample and obtaining a powder, extracting the powder and obtaining a ribonucleic acid (RNA), designing at least a pair of primer based on the RNA, amplifying the pair of primer and obtaining an amplified nucleic acid and quantifying the amplified nucleic acid using a quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) and obtaining a gene expression profile transcript characterize in that the RNA is from a de novo fatty acid biosynthetic gene protein coding region.